1994
DOI: 10.1007/bf00033881
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of anthraquinones in Morinda citrifolia cell suspensions

Abstract: Cell suspensions of Morinda citrifolia were cultivated in a B5-medium containing 4% sucrose as the sole carbon source and 1 mg 1-1 naphthyl acetic acid (NAA) or 1 mg 1-1 2,4-dichloro-phenoxyacetic acid (2,4-D). Both auxins were able to support growth but only in the presence of NAA anthraquinone production was observed. 2,4-D inhibited the production in NAA cultures. Anthraquinone synthesis took place in the growth and the stationary phase and amounts of 0.2--43.4 mmol (about 100-200 mg) g-1 dry weight could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…2c and 3c). One possible explanation is that replenishment of the medium in each subculture maintains the concentrations of ammonium at high level, which can inhibit the growth of the roots (George 1993). All these findings are in agreement with the results reported by Bulgakov et al (2002) which showed that total AQ production (mg l -1 of the medium) in Rubia cordifolia transgenic cultures was higher when a decrease of fresh biomass accumulation of the transgenic cultures was obtained.…”
Section: Resultssupporting
confidence: 85%
“…2c and 3c). One possible explanation is that replenishment of the medium in each subculture maintains the concentrations of ammonium at high level, which can inhibit the growth of the roots (George 1993). All these findings are in agreement with the results reported by Bulgakov et al (2002) which showed that total AQ production (mg l -1 of the medium) in Rubia cordifolia transgenic cultures was higher when a decrease of fresh biomass accumulation of the transgenic cultures was obtained.…”
Section: Resultssupporting
confidence: 85%
“…Similar results were reported by DeEknamkul and Ellis [21] where maximum rate of synthesis of rosamirinic acid in Salvia officinalis cell cultures occurred on addition of NAA. It is always desirable to use morphologically undifferentiated cells for the production of useful metabolites compared to intact plants [22]. In the present study, alkaloid contents in callus and suspension culture was higher than in the aerial parts of the plant.…”
Section: Root Regeneration In Semi Solid Mediummentioning
confidence: 46%